An optimized perovskite solar cell designs for high conversion efficiency - Hima, Abdelkader; Lakhdar, Nacereddine; Benhaoua, Boubaker; Saadoune, Achour; Kemerchou, Imad; Rogti, Fatiha (Superlattices and microstructures, 2019)
This paper reports the simulation and optimization of an organic/inorganic perovskite-based photovoltaic solar cell. Several structures for PSC are found in literature in order to enhance the conversion efficiency. The objectif of this work is to study and investigate different structures of solar cells based on perovskite materials to improve their performances. The simulated solar cell is made by sandwiching TiO2/Perovskite/spiro-OMeTAD layers where TiO2 is the electron transport layer (ETL), spiro-OMeTAD is the hole transport layer (HTL) and both CH3NH3PbI3 CH3NH3SnI3 are the perovskite (PVK) absorber layers. Therefore, the layer thicknesses of different materials are modified in order to find the better conversion efficiency of solar cells. The obtained results show that layer thicknesses that provide the maximum power conversion efficiency of 18.16% and 9.56% for both perovskite materials CH3NH3PbI3 and CH3NH3SnI3, respectively are 200 nm, 100 nm and 500 nm for spiro-OMeTAD, TiO2 and PVK materials, respectively. The numerical simulation was performed using the ATLAS device simulation software. ∗The effect of perovskite layer thickness on electrical parameters of perovskite-solar cells was investigated.∗The optimized layer thicknesses for ETL, HTL and PVK layer which provide the better power conversion efficiency are obtained.∗Power conversion efficiency of 18.16 % and 9.56 % for both optimized CH3NH3PbI3 and CH3NH3SnI3-based solar cell, respectively are achieved.